Hubungan pola komunikasi keluarga dengan perilaku merokok pada remaja - Saputra, Ahmad Diki; Hernanda , Rice (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Ikatan Perawat Kesehatan Komunitas Indonesia (IPKKI), 2024)
Background: The phenomenon of smoking in everyday life is often found in various places, including government institutions, public places and also schools and universities. According to the Central Statistics Agency, in 2022, 28.62% of the Indonesian population aged 15 years and over smoked, this percentage increased by 0.36% points from last year which was 28.26%. Based on gender, the percentage of men in the country who smoke reaches 56.36%. Meanwhile, only 1.06% of Indonesian women smoke. Factors causing smoking behavior in adolescents are knowledge, attitudes, ease of obtaining cigarettes, peer influence, and family communication patterns. Family communication patterns can be seen from how families, especially parents, form models for teenagers to smoke. Purpose: To analyze the relationship between family communication patterns and smoking behavior in adolescents. Methods: Quantitative research with analytical survey research design and cross sectional approach. The object of the research is family communication patterns and smoking behavior. The research subjects were teenagers at Darusy Syafa`Ah Vocational School, Gajah City, Lampung. The number of samples in the research was 52 respondents. The method used for sampling was the random sampling method. This research uses the chi square statistical test. Results: A total of 52 respondents were known to have the highest family communication patterns, namely 34 respondents (65.4%) in the functional communication category and the highest smoking behavior was 29 respondents (55.8%) in the negative smoking behavior category. The statistical results of the Chi square test obtained a p-value = 0.000 < 0.05, meaning that there is a significant relationship between family communication patterns and smoking behavior in adolescents. Conclusion: Statistical analysis using the chi-square method shows that there is a significant relationship between family communication patterns and smoking behavior in adolescents, with a p-value of 0.000 (p < 0.05) which indicates that good family communication patterns can be a protective factor in preventing smoking behavior in adolescents. Keywords: Communication Patterns; Smoking Behavior; Teenager Pendahuluan: Fenomena merokok dalam kehidupan sehari-hari sering sekali ditemukan diberbagai tempat, diantaranya lembaga pemerintahan maupun di tempat umum dan juga disekolah maupun universitas. Menurut Badan Pusat Statistik Tahun 2022 penduduk Indonesia berusia 15 tahun ke atas yang merokok sebesar 28,62% persentase tersebut meningkat 0,36% poin dari tahun lalu yang sebesar 28,26%. Berdasarkan jenis kelaminnya, persentase laki-laki di dalam negeri yang merokok mencapai 56,36%. Sementara, hanya 1,06% perempuan Indonesia yang merokok. Faktor penyebab terjadinya perilaku merokok pada remaja adalah pengetahuan, sikap, kemudahan mendapatkan rokok, pengaruh teman sebaya, dan pola komunikasi keluarga. Pola komunikasi keluarga bisa dilihat dari bagaimana keluarga terutama orang tua membentuk model bagi remaja untuk merokok. Tujuan: Untuk menganalisis hubungan antara pola komunikasi keluarga dengan perilaku merokok pada remaja. Metode: Penelitian kuantitatif dengan desain penelitian survey analitik dan pendekatan cross sectional. Objek penelitiannya adalah pola komunikasi keluarga dengan perilaku merokok. Subyek penelitiannya adalah Remaja di SMK Darusy Syafa`Ah Kota Gajah Lampung. Jumlah sampel dalam penelitian adalah sebanyak 52 responden. Metode yang digunakan untuk pengambilan sampel dengan menggunakan metode random sampling. Penelitian ini menggunakan uji stastitik chi square. Hasil: Sebanyak 52 responden diketahui pola komunikasi keluarga tertinggi yaitu 34 responden (65.4%) pada kategori komunikasi fungsional dan perilaku merokok tertinggi sebanyak 29 responden (55.8%) pada kategori perilaku merokok negatif. Hasil statistik uji Chi square diperoleh nilai p-value = 0,000 < 0,05 artinya terrdapat hubungan yang signifikan antara pola komunikasi keluarga dengan perilaku merokok pada remaja. Simpulan: Analisis statistik dengan metode chi-square menunjukkan adanya hubungan yang signifikan antara pola komunikasi keluarga dan perilaku merokok pada remaja, dengan nilai p-value sebesar 0,000 (p < 0,05) yang mengindikasikan bahwa pola komunikasi keluarga yang baik dapat menjadi faktor protektif dalam mencegah perilaku merokok pada remaja. Kata Kunci : Perilaku Merokok; Pola Komunikasi; Remaja